Peranan Pembiayaan Bank Syariah Dalam Meningkatkan Usaha Mikro Dan Menengah Studi Kasus BSI KCP Pati - Imam Fatoni (Genius: Jurnal Ekonomi Dan Manajemen, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, especially in creating jobs and improving people's welfare. However, one of the main obstacles faced by MSMEs is access to capital. In this context, Islamic financing is a significant alternative for MSMEs to obtain financial support without having to rely on the interest-based conventional banking system. This study aims to analyse the role of Bank Syariah Indonesia (BSI) Pati Sub-Branch Office (KCP) financing in improving the sustainability and growth of MSMEs. This research uses a quantitative approach with a case study method. The data sources in this study include primary data obtained from interviews with MSME actors who received financing from BSI KCP Pati, as well as secondary data from BSI annual reports and related academic publications. The results showed that the majority of MSMEs experienced a significant increase in production capacity and income after obtaining Islamic financing. Financing schemes such as musyarakah and mudharabah provide more flexible and fair benefits for businesses compared to interest-based credit systems. In addition to the positive impact on business growth, this study also identifies several challenges in the application of Islamic financing, such as the lack of understanding of the Islamic financial system among businesses and the complex application procedures. Thus, education efforts and increased Islamic financial literacy for MSME players are needed so that the benefits of this financing can be accessed more widely and optimally. The results of this study are expected to contribute to the development of Islamic financial policies and increase the effectiveness of financing for MSMEs in Indonesia.